2017
DOI: 10.1021/acs.jpcc.6b09722
|View full text |Cite
|
Sign up to set email alerts
|

Ag Doping of Organometal Lead Halide Perovskites: Morphology Modification and p-Type Character

Abstract: We report a simple synthetic approach to grow uniform CH3NH3PbI3 perovskite (PSK) layers free of pinholes via varied portions of silver iodide (AgI) added to the precursor solution. XRD/EDS elemental mapping experiments demonstrated nearly uniform Ag distribution inside the perovskite film. When the 1% AgI-assisted perovskite films were fabricated into a p-i-n planar device, the photovoltaic performance was enhanced by ∼30% (PCE increased from 9.5% to 12.0%) relative to the standard cell without added AgI. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…Therefore, the observed dark current change of lateral structure devices merely comes from the surface doping of perovskites by the adsorption of metal ion impurities with perovskite surfaces. Ag + and Sr 2+ ions have been introduced into hybrid perovskite solar cells as additives to enhance the efficiency of solar cells 36 39 . It should also be noted the XRD peak shift of polycrystalline films cannot be simply explained by metal ion incorporation into perovskite lattice, unless the complexity of strain distribution in perovskite films could be well excluded 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the observed dark current change of lateral structure devices merely comes from the surface doping of perovskites by the adsorption of metal ion impurities with perovskite surfaces. Ag + and Sr 2+ ions have been introduced into hybrid perovskite solar cells as additives to enhance the efficiency of solar cells 36 39 . It should also be noted the XRD peak shift of polycrystalline films cannot be simply explained by metal ion incorporation into perovskite lattice, unless the complexity of strain distribution in perovskite films could be well excluded 40 .…”
Section: Resultsmentioning
confidence: 99%
“…X-ray Photoelectron Spectroscopy (XPS) data conrm the presence of additives in the prepared lm and interfaces as well as a band shi; however, it is not clear yet whether they are incorporated as dopants or not. Shahbazi et al reported an enhanced hole extraction and device efficiency by the addition of AgI to the precursor solution 128 and Yang et al reported increased p-type conductivity in MAPbI 3 aer the addition of NaI to the precursor solution. 134 Additional monovalent cation precursors, i.e., CsI, KI and RbI, are implemented in a recently reported cation cascade mixed perovskite 135 with enhanced stability and performance in which they are supposed to replace the A-site MA + or formamidinium (FA + ) cations in the perovskite lattice.…”
Section: Lead Partial Exchange With Monovalent Metalsmentioning
confidence: 99%
“…Trivalent metal ions doping (Al 3+ , Bi 3+ , Sb 3+ , In 3+ ) is beneficial to the crystal growth of perovskite films with suppressed microstrain and reduced defects . And monovalent cations of Cu + , Na + , and Ag + were also introduced into the CH 3 NH 3 PbI 3 to tune the morphological, optical, and electrical properties of perovskite films . Although positive effect and great promotion on the progress of PSCs have been achieved by metal cation doping with various valence, the behind nature of doping mechanism especially from the viewpoints of polarity and mobility, is not yet completely clarified.…”
Section: Introductionmentioning
confidence: 99%